Legal Protection For Creditors Related To The Existence Of Unregistered Fiduciary Guarantee Deeds In The Event Of Debtor Defaults (Study Case District Decision Number 108/Pdt.G/2021/Pn.Mks) - Febe Hartanto (Authentica: Private Law Journal, 2025)
This research was conducted on the decision of the Makassar District Court civil case number 108/Pdt.G/2021/PN.Mks is concerned about a default lawsuit against a loan agreement that has been guaranteed with fiduciary guarantee and personal guarantee. In the decision, there was a problem where the fiduciary guarantee deed had not yet been registered. Therefore, even if the judges declares that the debtor is in default, the plaintiff or the creditor still cannot execute the fiduciary guarantee based on the fiduciary guarantee certificate. The purpose of this study is to analyze the consequences and the legal protection for the creditor related to the fiduciary guarantee deed that is not registered. This study uses a normative juridical research type, with the specifications of the research carried out in a prescriptive manner. The legal sources taken in this research came from secondary data which include primary and secondary legal materials with the data collection method through literature study. From this study, 2 (two) conclusions were obtained which the first one showed that the consequences of not registering the fiduciary guarantee deed is there is no fiduciary guarantee so that the agreement is just an ordinary loan agreement, therefore the position of the creditor is only as a concurrent creditor and there is no material character such as droit de suite and preferential rights attached to the fiduciary creditor. Apart from that, the creditor also does not have the right to executorial power based on the fiduciary guarantee certificate. Second, in terms of the debtor defaults, then the legal protection for the creditor if they feel aggrieved and want to claim or demand the debt back, they can only sue based on Article 1131 of the Civil Code.